2015
DOI: 10.1371/journal.pone.0129014
|View full text |Cite
|
Sign up to set email alerts
|

Performance Development in Adolescent Track and Field Athletes According to Age, Sex and Sport Discipline

Abstract: IntroductionSex-specific differences that arise during puberty have a pronounced effect on the training process. However, the consequences this should have for goal-setting, planning and implementation of training for boys and girls of different ages remains poorly understood. The aim of this study was to quantify performance developments in athletic running and jumping disciplines in the age range 11-18 and identify progression differences as a function of age, discipline and sex.MethodsThe 100 all-time best … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
85
2
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(99 citation statements)
references
References 28 publications
9
85
2
3
Order By: Relevance
“…The present study shows that the gender divergence in performance for swimming and for running and jumping track and field events is very closely aligned to the timing of the onset of male puberty, which typically has onset at around 12 years of age . These findings are consistent with reports on the timing of the gender differences in performance observed among Norwegian athletes in two running and two jumping events and for track and field skills among Polish athletes . This study extends the findings to swimming and a wider range of running and jumping track and field events.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The present study shows that the gender divergence in performance for swimming and for running and jumping track and field events is very closely aligned to the timing of the onset of male puberty, which typically has onset at around 12 years of age . These findings are consistent with reports on the timing of the gender differences in performance observed among Norwegian athletes in two running and two jumping events and for track and field skills among Polish athletes . This study extends the findings to swimming and a wider range of running and jumping track and field events.…”
Section: Discussionsupporting
confidence: 90%
“…After completion of male puberty, circulating testosterone levels in men are consistently 10‐15 times higher than in children or women at any age . The age at which sex differences emerge is reported as around the age of 12 from a study of individual Norwegian athletes in two running and two jumping events and at 13‐14 years in four track and field skills in Polish athletes; however, the relationship to male puberty and circulating testosterone is not clear. This study investigates the age of the gender divergence in performance in elite swimming and a wider range of elite athletic events as well as a community‐based study of grip strength among nonathletes to deduce the onset and progression of the gender divergence in performance of athletes and relates this to the timing and tempo of male puberty and the rise in circulating testosterone into adult male levels.…”
Section: Introductionmentioning
confidence: 99%
“…However, beyond this age, male athletes outperform female athletes. 25 It is important to note that the age of peak performance has changed in recent decades in female but not in male athletes. In the last 20-30 years, ages at which peak athletic performance is observed have increased in female but not in male athletes.…”
Section: Athletes In Younger Age-groups Were Faster Than Athletes Imentioning
confidence: 99%
“…That said, as athletes reach adolescence and males develop more rapidly, the performance gap between genders increases (Malina et al, 2010). In their study on the performance developments of track and field athletes, Tønnessen, Svendsen, Olsen, Guttormsen, and Haugen (2015) found that "the 800 m performance sex difference evolves from 4.8% at the age of 11 to 15.7% at the age of 18" (p. 5). The authors recommend that coaches consider these differences when planning performance goals for athletes.…”
Section: Gender Differencesmentioning
confidence: 99%